A new Laplace transformation method for dynamic testing of solar collectors. (March 2015) - Kong, Weiqiang; Perers, Bengt; Fan, Jianhua; Furbo, Simon; Bava, Federico
Abstract: A new dynamic method for solar collector testing is developed. It is characterized by using the Laplace transformation technique to solve the differential governing equation. The new method was inspired by the so called New Dynamic Method (NDM) (Amer E. et al (1999) [1]) but totally different. By integration of the Laplace transformation technique with the Quasi Dynamic Test (QDT) model (Fischer S. et al (2004) [2]), the Laplace – QDT (L-QDT) model is derived. Two experimental methods are then introduced. One is the shielding method which needs to shield and un-shield solar collector continuously during test period. The other is the natural test method which doesn't need any intervention. The new L-QDT model with the shielding method are tested by TRNSYS (Klein S. et al (1988) [3]) simulation. Experiments were carried out at Technical University of Denmark by using the L-QDT method and the natural experimental method. The identified collector parameters are then compared and analyzed with those obtained by the steady state test method and the QDT test method. The results comparison shows that the L-QDT method and the natural experimental method are also valid. It can be concluded that the new Laplace test method can obtain reasonable and accurate collector parameters under transient weather condition. Highlights: We developed a new dynamic test method for solar collectors. We introduced two experimental test methods. The new method is verified both by TRNSYS simulation and experiments. The test results show good agreement with the steady state test method.